Accuracy of self‐reported smoking cessation during pregnancy. (13th November 2014) - Tong, Van T.; Althabe, Fernando; Alemán, Alicia; Johnson, Carolyn C.; Dietz, Patricia M.; Berrueta, Mabel; Morello, Paola; Colomar, Mercedes; Buekens, Pierre; Sosnoff, Connie S.; the Prenatal Tobacco Cessation Intervention Collaborative:; Farr, Sherry L.; et al.
Abstract Evidence of bias of self‐reported smoking cessation during pregnancy is reported in high‐income countries but not elsewhere. We sought to evaluate self‐reported smoking cessation during pregnancy using biochemical verification and to compare characteristics of women with and without biochemically confirmed cessation in Argentina and Uruguay. In a cross‐sectional study from October 2011 to May 2012, women who attended one of 21 prenatal clinics and delivered at selected hospitals in Buenos Aires, Argentina and Montevideo, Uruguay, were surveyed about their smoking cessation during pregnancy. We tested saliva collected from women <12 h after delivery for cotinine to evaluate self‐reported smoking cessation during pregnancy. Overall, 10.0% (44/441) of women who self‐reported smoking cessation during pregnancy had biochemical evidence of continued smoking. Women who reported quitting later in pregnancy had a higher percentage of nondisclosure (17.2%) than women who reported quitting when learning of their pregnancy (6.4%).